2011
DOI: 10.1186/1476-7961-9-9
|View full text |Cite
|
Sign up to set email alerts
|

The clinical implications of adult-onset henoch-schonelin purpura

Abstract: Henoch-Schonlein Purpura (HSP) is a small vessel vasculitis mediated by IgA-immune complex deposition. It is characterized by the clinical tetrad of non-thrombocytopenic palpable purpura, abdominal pain, arthritis and renal involvement. Pathologically, it can be considered a form of immune complex-mediated leukocytoclastic vasculitis (LCV) involving the skin and other organs. Though it primarily affects children (over 90% of cases), the occurrence in adults has been rarely reported. Management often involves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 44 publications
0
54
0
1
Order By: Relevance
“…1 However, HSP can be seen at any age, though the occurrence in adults is rare and reported in 3.4 -14.3 cases per million. 3 The precise etiology of HSP is unknown. The proposed triggers are generally infectious; an upper respiratory infection often precedes HSP symptoms in 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 However, HSP can be seen at any age, though the occurrence in adults is rare and reported in 3.4 -14.3 cases per million. 3 The precise etiology of HSP is unknown. The proposed triggers are generally infectious; an upper respiratory infection often precedes HSP symptoms in 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…IgA complex depositions accumulate primarily in the skin, intestinal mucosa, joints and kidneys-precisely the organ systems behind the classic clinical features of HSP. 3 The main clinical features seen with HSP are palpable purpura, abdominal pain, arthritis, and renal insufficiency. A retrospective analysis of 250 adult patients with HSP reported a purpuric rash in 96% of cases, arthritis in 61%, gastrointestinal disease in 47%, and renal disease in 32%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This systemic vasculitis is characterized by palpable purpura, arthritis or arthralgias, gastrointestinal and renal involvement. 1,2 It has been shown that multiple different genes and their interactions with environmental factors are involved in the susceptibility to HSP. 3 Therefore, genetic background is an important factor in the pathogenesis of this immune-mediated inflammatory disease.…”
mentioning
confidence: 99%